ANALISIS KEMAMPUAN KEUANGAN DAERAH KABUPATEN SIGI SEBAGAI DAERAH OTONOM BARU HASIL PEMEKARAN - Alvianto, Fredi; Amir, Andi Mattulada; Fattah, Vita Yanti (Katalogis, 2018)
Study on financial ability of Sigi Regency as new autonomous region resulting from regional proliforation has been carried out. The present study, the financial ability region is measured by 1). Fiscal Decentralization Degree (DDF) 2). Fiscal Need 3). Fiscal Capacity 4). Fiscal Effort 5). Effectiveness of Local Revenue 6). Region Financial Indenpendency Ratio used data from 2010 to 2015. The result exhibited that financial ability of Sigi Regency is very low, so that the dependence of financial with central goverment is still very high.